Intercultural representations of Germany and their impact on academic mobility - Chin, Ee Wen (2017)
There has been a lot of debate among researchers on intercultural activities of crossborder mobility (Dervin, 2011, Henze and Zhu, 2012, Machart and Lim, 2013). Since the word ‘culture’ is used to put people in different categories and create culturally different Others, the question arises whether it can explain all intercultural activities in mobile students’ experiences or do they represent occurrences of “interculturality without culture?” (Dervin 2010). The study of ‘intercultural’ activities should focus on the experiences and interactions between individuals, and cultural identification processes of interculturality should not refer to any kind of static ‘culture’ during the sojourn. According to Dervin & Machart (2015), it is believed that social and personal representations of the Other’s culture impact attitudes and subsequently behaviours. In this study, a liquid intercultural approach is employed to examine how Malaysian students represent themselves, Germany and German speakers, and the impact of this representation on student mobility. Interviews were conducted with students in the B.A German programme in Malaysia who took part in a cross-border academic mobility programme in Germany, as well as with students who did not take part in any mobility programme. Participants were asked on their representations of Germany and German speakers, and their motivation to participate in the mobility programme. Students who have been to Germany were also asked on their ‘intercultural’ encounters in the host country. Using Mixed Intersubjectivity (Dervin,2013), the analysis would entail how participants identified themselves as non-native language learners and how they perceived Germany, the impact of their representations on their motivation to study abroad and how mobile participants faced interculturality when they were in Germany. The focus of the study is on how the participants talked instead of what they said about themselves, the Other and the encounters they made. This will reveal the power relations between the language learners and the native speakers from the mobile students’ point of view.